Konflik Batin Tokoh Utama dalam Cerpen Sumur Sebuah Cerita Karya Eka Kurniawan : Kajian Psikologi Sastra - Intan Nibrosy Rubyssalam; Muhajir Muhajir; Ahmad Rifai (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to: (1) analyze the inner conflict experienced by the main characters Toyib and Siti, (2) the factors causing the conflict experienced by the main characters, (3) the responses taken by the main characters, (4) the plot in the short story Sumur Sebuah Cerita by Eka Kurniawan. The method used is descriptive qualitative with a literary psychology approach, which allows researchers to explore the psychological aspects of the characters based on psychological theories, especially those related to inner conflict. The techniques used are literature study, reading and note-taking techniques. The instrument used is a data card for classifying the form of inner conflict. The results of the study show that the main characters experience various forms of inner conflict, such as depression, anxiety, fear, feelings of inadequacy, frustration, anger, guilt, and concern. These inner conflicts arise as a result of interpersonal relationships, social conditions, and environmental situations that are not supportive, such as water crises and poverty. The factors causing this inner conflict include differences between individuals and clashes of interests. The responses taken by the characters to the conflict are through selection and rejection, hesitation or indecision, and compromise.